2016
DOI: 10.1113/ep085772
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic cerebral autoregulation is unrelated to decrease in external carotid artery blood flow during acute hypotension in healthy young men

Abstract: New Findings r What is the central question of this study?Dynamic cerebral autoregulation (CA) is impaired by sympathetic blockade, and the external carotid artery (ECA) vascular bed may prevent adequate internal carotid artery blood flow. We examined whether α 1 -receptor blockade-induced attenuation of dynamic CA is related to reduced ECA vasoconstriction. r What is the main finding and its importance? α 1 -Receptor blockade attenuated dynamic CA, but in contrast to our hypothesis did not affect the ECA bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
33
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 33 publications
7
33
0
Order By: Relevance
“…Our studies also suggest that the intracranial vasculature is 'defended' against acute changes by varying ECA vascular responses during acute central hypovolaemia and hypervolaemia or hypotension or hypertension (Sato et al 2011;Ogoh et al 2013Ogoh et al , 2014Ogoh et al , 2016Hirasawa et al 2016). In addition, Aratow et al (1991) demonstrated that a postural change from 60 deg head-up tilt to −6 deg head-down tilt increased forehead cutaneous flow (ß26%) significantly.…”
Section: Cerebral Blood Flow Distribution During Acute Microgravitymentioning
confidence: 53%
See 1 more Smart Citation
“…Our studies also suggest that the intracranial vasculature is 'defended' against acute changes by varying ECA vascular responses during acute central hypovolaemia and hypervolaemia or hypotension or hypertension (Sato et al 2011;Ogoh et al 2013Ogoh et al , 2014Ogoh et al , 2016Hirasawa et al 2016). In addition, Aratow et al (1991) demonstrated that a postural change from 60 deg head-up tilt to −6 deg head-down tilt increased forehead cutaneous flow (ß26%) significantly.…”
Section: Cerebral Blood Flow Distribution During Acute Microgravitymentioning
confidence: 53%
“…MCA) using transcranial Doppler. However, we have recently demonstrated that there is a heterogeneous CBF response in cerebral arteries during several physiological conditions, and the data of these previous studies suggested that these heterogeneous CBF responses might help to maintain circulatory homeostasis in the brain (Sato et al 2011;Ogoh et al 2013Ogoh et al , 2014Ogoh et al , 2016Hirasawa et al 2016). There are two principal arteries that supply blood to the brain, namely the common carotid (CCA) and the vertebral arteries (VA).…”
Section: Introductionmentioning
confidence: 99%
“…It is not known what happens to the distribution of Q in spaceflight. The normal response to upright posture is a reduction in splanchnic blood flow (26), while brain blood flow (19) and resting leg blood flow (32) can be reduced. With long-duration spaceflight, blood flow is unchanged from preflight in the femoral and cerebral arteries compared with supine baseline (3).…”
Section: Discussionmentioning
confidence: 99%
“…Baroreflex acts for example on the total peripheral resistance by modulating sympathetic nerve activity. However, the sympathetic effect on the extracranial vascular bed and the relations between the intracranial and extracranial circulations are not completely understood [4]. A better understanding of the intracranial and extracranial hemodynamics may improve the assessment of the intracranial state by non-invasive, yet superficial tissue dependent, extracranial measurements such as functional Near-Infrared Spectroscopy [57] and noninvasive intracranial pressure (ICP) monitoring by strain gauge [8].…”
Section: Introduction and Motivationsmentioning
confidence: 99%
“…The authors in [3,4] recorded the blood flow at the internal (ICA) and external carotid (ECA) arteries during a bout of acute hypotension caused by thigh-cuff inflation-deflation. The ICA blood flow dropped (26.7% in [3], 16.8% in [4]-control) and returned rapidly to baseline levels thanks to CA and baroreflex, showing an overshoot (23.8% in [3], 8.1% in [4]-control) followed by an oscillatory behavior in [3].…”
Section: Introduction and Motivationsmentioning
confidence: 99%